PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN LAPTOP MEREK TOSHIBA DI SEMARANG - Pinassang, Andree Weinard; Rahardjo, Susilo Toto (Diponegoro Journal of Management, 2017)
The purpose of this research is to analyze the influence of brand awareness, brand associations, quality perceptions and brand loyalty to purchase decision of Toshiba Brand Top Lap.The population used is consumers who purchase Toshiba brand lap tops in Semarang whose numbers are unknown. Samples taken 100 consumers. The type of data used in the primary data. Methods of data collection questionnaire. The analyze technique used is multiple regression, with previously tested by instrument test and classical assumption test.The results showed that: Brand awareness proved impact positive and significant on purchase decisions. Brand association proved impact positive and significant on purchase decisions. Quality perceptions proved impact positive and significant on purchase decisions. Brand loyalty proved impact positive and significant on purchase decisions.